2020
DOI: 10.1057/s41599-020-00595-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of legal expertise on moral decision-making biases

Abstract: Traditional and mainstream legal frameworks conceive law primarily as a purely rational practice, free from affect or intuition. However, substantial evidence indicates that human decision-making depends upon diverse biases. We explored the manifestation of these biases through comparisons among 45 criminal judges, 60 criminal attorneys, and 64 controls. We examined whether these groups’ decision-making patterns were influenced by (a) the information on the transgressor’s mental state, (b) the use of gruesome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 107 publications
2
9
0
1
Order By: Relevance
“…This suggests that evaluators weighted factors that have lower empirical support less in rendering judgments, which is encouraging. The lower effect size for florid details is consistent with recent research showing that those who work in the legal field (i.e., judges and attorneys) are less influenced by gruesome details when rating moral wrongness or assigning punishment in written scenarios involving harm to a victim (Baez et al, 2020). Also in line with our expectations, average risk ratings and likelihood for recommending commitment increased incrementally, as additional indicators were included in the vignettes.…”
Section: Resultssupporting
confidence: 90%
“…This suggests that evaluators weighted factors that have lower empirical support less in rendering judgments, which is encouraging. The lower effect size for florid details is consistent with recent research showing that those who work in the legal field (i.e., judges and attorneys) are less influenced by gruesome details when rating moral wrongness or assigning punishment in written scenarios involving harm to a victim (Baez et al, 2020). Also in line with our expectations, average risk ratings and likelihood for recommending commitment increased incrementally, as additional indicators were included in the vignettes.…”
Section: Resultssupporting
confidence: 90%
“…Criminal judges such as judges, classically face difficult decisions as they must assess complex information sources, and they need to integrate all those sources to try to provide fair and justice decisions 2 . Crucially, although previous studies have found that resting HRV in criminal judges could predict moral decision making 2 , no studies have assessed to what extent the resting HRV could track behavior in social decision-making paradigms which require strategic behavior to maintain fairness and reciprocity 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Criminal judges such as judges, classically face difficult decisions as they must assess complex information sources, and they need to integrate all those sources to try to provide fair and justice decisions 2 . Crucially, although previous studies have found that resting HRV in criminal judges could predict moral decision making 2 , no studies have assessed to what extent the resting HRV could track behavior in social decision-making paradigms which require strategic behavior to maintain fairness and reciprocity 5 . Based on this context, in this study, we assessed the behavior of a group of criminal judges (with an average of 14 years (SD = 9.1) of expertise in legal scenarios) conducting a social decision-making task (UG) compared to a control group (individuals without legal expertise).…”
Section: Introductionmentioning
confidence: 99%
“…А это, в свою очередь, несет прямую угрозу самой идее беспристрастного правосудия. В то же время есть экспериментальные данные о том, что опыт профессиональной юридической практики, в том числе судейской, позволяет преодолеть по крайней мере некоторые из таких предубеждений [Baez et al, 2020]. Таким образом под черкивается важность специальных компетенций в принятии правовых решений.…”
Section: мораль и закон: проблема соотношенияunclassified